Image Transmission Through MC-CDMA Channel: An Image Quality Evaluation - Oh, Tick Hui; Tan, Kim Geok (World Scientific Publishing Co Pte Ltd, 2008)
The multicarrier code division multiple access (MC-CDMA) system is considered as an advancement in mobile communication system. Seen as the next generation communication technology after the 3G, signals can be easily transmitted and received using the Fast Fourier Transform (FFT) device without increasing the transmitter and receiver complexities.